‘Al aire sombrearé lo transparente’: los anteojos de sor Juana Inés de la Cruz y su arte político tras la cámara oscura: tecnologías de la imagen y virtualidad en el auto sacramental El mártir del Sacramento, San Hermenegildo - Llosa Sanz, Alvaro (Diálogos Latinoamericanos, 2022)
In scenes VII-X of the second painting corresponding to the ‘auto sacramental’ The martyr of the Sacrament, San Hermenegildo by Sor Juana Inés de la Cruz (1651-1695), the character who allegorizes the fantasy of King Leovigildo visibly projects the series of Hispanic Gothic kings in the theatrical space. This visibility generated by the right of fantasy perfectly fulfills the requirements of visual composition ascribed to the art of memory in the Golden Age and even visibly communicates the dramatic architecture of the glorifying discourse of the monarchy implicit in such staging. They make up a theater of memory that, gestated from the emblematic and Golden Age programmatic culture of the galleries of fame, is fantastically staged before the eyes of the audience. The set of scenes is also inscribed in the political-religious theme of Visigothic Arianism and the question of the conversion of the monarchy to Catholic Christianity represented by Hermenegildo, crown prince. I am interested in addressing, in the colonial context of Sor Juana, how the projection of these virtual and hologrammatic images produced in the theatrical space correspond and dialogue both with the hermetic thought of political emblems and occhiali and with the optical technologies of the time, especially the camera obscura, which could be considered as a new tool at the service of the tradition of the art of memory and reaches our days in form. of cinematography and other virtual visual projections.